1965
DOI: 10.1083/jcb.25.2.193
|View full text |Cite
|
Sign up to set email alerts
|

THE ULTRASTRUCTURE OF COTYLEDONARY TISSUE FROM GOSSYPIUM HIRSUTUM L. SEEDS

Abstract: Quiescent cottonseeds stored in a dry, anaerobic situation for over a year have been shown to contain cells whose contents are ultrastructurally similar to those of normal, fully hydrated plant cells. Plastids, mitochondria, and nuclei of the cells of cotyledon tissue in dry seeds possess normal-looking double membranes even under conditions of extreme desiccation. Previous reports have indicated on the basis of light microscopic work, that the cells of certain dry seeds do not possess nuclear membranes or mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
47
0
1

Year Published

1966
1966
1972
1972

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 19 publications
2
47
0
1
Order By: Relevance
“…Indeed, the membranes bounding spherosomes are not visible following permanganate fixation (24) and have confused a great many microscopists using other fixatives (9). Perhaps the appellation "interfacial structure" (14) might have been a more appropriate choice, since interfacial structures similar to these single-line membranes exist around certain fat droplets of artificially prepared emulsions.…”
mentioning
confidence: 99%
“…Indeed, the membranes bounding spherosomes are not visible following permanganate fixation (24) and have confused a great many microscopists using other fixatives (9). Perhaps the appellation "interfacial structure" (14) might have been a more appropriate choice, since interfacial structures similar to these single-line membranes exist around certain fat droplets of artificially prepared emulsions.…”
mentioning
confidence: 99%
“…The affinity of spherosomes for lipophilic stains (6) and the relative abuindance of spherosomes in the storage tissuie of oil seeds (22) Electron Microscopy. Isolated spherosomes were embedded in an agar medium to facilitate manipulation through the fixation procedures.…”
mentioning
confidence: 99%
“…(1963), Horncr S: Arnott (1965), Pcrncr (1965a and, Siniola (1969) and Yatsu (1965). Opik (1966), who studicd the finc structure of Pkaseoliis cotyledons during germination, found that thc storage cclls containcd, among other things, protein bodies, 2-22 ii in diamctcr and surrounded by a unit mcmbranc.…”
Section: Discussionmentioning
confidence: 99%